2009
DOI: 10.1007/s10067-009-1238-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of 22 cytokine gene polymorphisms with rheumatoid arthritis in population of ethnic Macedonians

Abstract: To examine the possible role of 22 cytokine gene polymorphisms in host susceptibility to or protection against RA in Macedonians. In this study, 301 healthy unrelated individuals and 85 patients with RA were studied. Cytokine genotyping was performed by PCR with sequence-specific priming (PCR-SSP) (Heidelberg kit). Results showed susceptible association for four cytokine alleles, six cytokine genotypes, one haplotype, and four combinations of haplotypes, while protective associations were found for four cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
70
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 16 publications
10
70
2
3
Order By: Relevance
“…Healthy subjects were recruited from the patient pool at the Clinic for Oral Diseases and Periodontology, University Clinical Centre of Stomatology, Skopje, Macedonia (17)(18)(19). All subjects were over 20 years of age, had at least 20 teeth present, were from Macedonian ethnic background to the third generation, and were unrelated residents from different geographical regions of the Republic of Macedonia.…”
Section: Methodsmentioning
confidence: 99%
“…Healthy subjects were recruited from the patient pool at the Clinic for Oral Diseases and Periodontology, University Clinical Centre of Stomatology, Skopje, Macedonia (17)(18)(19). All subjects were over 20 years of age, had at least 20 teeth present, were from Macedonian ethnic background to the third generation, and were unrelated residents from different geographical regions of the Republic of Macedonia.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, an earlier study carried out in patients with pulmonary TB revealed that the combination of the IFNG +874 polymorphism and allele A homozygosity was associated with significantly lower levels of IFNG compared to those in individuals carrying one or two copies of the T allele 7,8 .…”
Section: Introductionmentioning
confidence: 92%
“…Several polymorphisms in the promoter region of the IFN-γ gene (IFNG), in particular those at position +874, are considered to influence the levels of expression of this cytokine. Several studies have demonstrated the association of this single nucleotide polymorphism (SNP) with susceptibility towards, and severity of, this disease 7,8 . Local and systemic IFN-γ levels correlate with TB severity.…”
Section: Introductionmentioning
confidence: 99%
“…The study of cytokine gene polymorphisms is a helpful tool to predict the genetic susceptibility to diseases in special communities. Polymorphism in cytokine genes are known to influence cytokine levels and may also be associated with susceptibility/resistance to tuberculosis or outcome and clinical forms of this disease (9)(10)(11)(12)(13). The pattern of cytokine gene polymorphisms is different in various populations (14).…”
Section: Introductionmentioning
confidence: 99%